2020
DOI: 10.1029/2020jc016436
|View full text |Cite
|
Sign up to set email alerts
|

Weak Response of Biological Productivity and Community Structure of Phytoplankton to Mesoscale Eddies in the Oligotrophic Philippine Sea

Abstract: In general, eddies could play a role in the transport of biogeochemical constituents, as well as in anomalous water properties in the region (e.g., Aguilar-Islas et al., 2013; McGillicuddy et al., 1998, 2003). Previous studies found that eddies can deliver episodic pulses of deep-layer nutrients to the euphotic zone and thus affect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 67 publications
3
14
0
Order By: Relevance
“…These are equivalent to 210 and 130 mg C m −2 d −1 , assuming a photosynthetic quotient of 1.4 (Laws, 1991). Given that the typical 18 O-GPP/ 14 C-NPP value range is 2.0-2.7 (Marra, 2002;Quay et al, 2010), these values are consistent with the NPP value of 76-80 mg C m −2 d −1 measured using the 13 C incubation method in the study region in 2018 (Yun et al, 2020).…”
Section: Extreme Oligotrophy Of the Northwest Pacificsupporting
confidence: 77%
“…These are equivalent to 210 and 130 mg C m −2 d −1 , assuming a photosynthetic quotient of 1.4 (Laws, 1991). Given that the typical 18 O-GPP/ 14 C-NPP value range is 2.0-2.7 (Marra, 2002;Quay et al, 2010), these values are consistent with the NPP value of 76-80 mg C m −2 d −1 measured using the 13 C incubation method in the study region in 2018 (Yun et al, 2020).…”
Section: Extreme Oligotrophy Of the Northwest Pacificsupporting
confidence: 77%
“…This large difference in primary production may be associated with environmental conditions such as light intensity and nutrients (Pabi et al, 2008;Tremblay et al, 2015;Lee et al, 2019;Zheng et al, 2021). Prior to this study, Yun et al (2020) observed that picophytoplankton, the presence of which indicates a nutrient-deficient state, were the predominant phytoplankton groups despite the occurrence of mesoscale eddies supplying nutrients to the euphotic layer in the Philippine Sea. Our results on the phytoplankton community also indicated that picophytoplankton, containing P r o ch l o r oc oc cu s a n d S y n e c h o c o c c u s , wa s a m a jo r phytoplankton group in the Philippine Sea, suggesting that nutrients were limited at both light depths.…”
Section: Vertical Distribution Characteristics Of Primary Production ...mentioning
confidence: 61%
“…Additionally, Ting et al (2002) described how Prochlorococcus is particularly efficient in absorbing enriched blue light at depth compared with Synechococcus, and this light absorption ability gives Prochlorococcus a competitive advantage under low light conditions. Although nutrients are also an important factor in the survival and competition of phytoplankton, Yun et al (2020) observed a weak impact of nutrient supplies in mesoscale eddies on phytoplankton community composition in the Philippine Sea. This light adaptation in photosynthetic pigments determines the competitive advantages of each phytoplankton group, and it may contribute to the phytoplankton community structure at different depths in oligotrophic oceans.…”
Section: Introductionmentioning
confidence: 95%
“…Xu et al (2019) reported that ~5,000 eddies were detected in the NWP over 20 years , with a mean lifespan of ~7 weeks and a mean speed of 6 km d −1 westward. Yun et al (2020) reported no clear differences in phytoplankton biomass and PP between the outer area of the eddies and the mesoscale eddies in the tropical NWP.…”
Section: Introductionmentioning
confidence: 91%